"And it was all my choice but it didn't feel like a choice": A re-examination of interpretation of data using a 'rhetoric of choice' lens. (November 2015) - Frost, Nollaig; Rodriguez, Deborah
Synopsis: This research aims to re-examine interpretations of data collected from second-time mothers about their experiences of becoming a mother to a second child using lenses of 'rhetoric of choice' and 'choice feminism'. The interpretations are reconsidered to identify ways in which tensions between maternal status and researcher positionality have influenced the ways they were reached. The paper describes two studies, each conducted by one of the authors, and the interpretations of the data made at the time the research was carried out. It discusses alternative interpretations and how they challenge both the researcher role and theoretical explanations of gender inequity and attachment. The paper concludes that feminist research can be strengthened by attending to the intersections between maternal status, and positioning as feminist, woman and researcher. Highlights: Retrospectively considers data interpretations using feminist lenses Highlights salience of maternal status in feminist research Considers tensions between feminist research and researcher positionality